2015
DOI: 10.1007/s11663-015-0360-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Eddy Effect of Coils on Flow and Temperature Fields of Molten Droplet in Electromagnetic Levitation Device

Abstract: In this work, the influence of eddy effect of coils on magnetic, flow, and temperature fields in an electromagnetically levitated molten droplet was investigated by a serial of axisymmetric numerical simulations. In an electromagnetic levitation device, both metal droplet and coils are conductive materials, therefore the distributions of current density in them should be nonuniform as a result of the eddy effect. However, in previous works, the eddy effect was considered alone in metal droplet but ignored in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…2. 26) Obviously, both the lifting force and absorbed power show well consistence with those in Ref. 10).…”
Section: Model Validationsupporting
confidence: 77%
See 3 more Smart Citations
“…2. 26) Obviously, both the lifting force and absorbed power show well consistence with those in Ref. 10).…”
Section: Model Validationsupporting
confidence: 77%
“…Through submitting Lorentz force and absorbed power into Navier-Stokes equations and energy equation respectively, the flow field and temperature field inside a fixed sphere can be obtained. 26) Figure 3 shows such a case and we compared our results with those in Ref. 10).…”
Section: Model Validationmentioning
confidence: 95%
See 2 more Smart Citations
“…Feng and Shi developed a FEM model to investigate the effect of eddy currents inside the coil on the sample temperature. [42] They also modeled the internal fluid flow in the spherical sample and found that the temperature is not homogeneous but can vary up to 0.1 K within the sample. Later, they developed a model using the arbitrary Lagrangian-Eulerian (ALE) finite element technique, which has the main advantage that the computational mesh inside the domains can move arbitrarily to optimize the shapes of elements and follow the contours of moving materials.…”
mentioning
confidence: 99%